Impact of Covid 19 on Family Financing and Family Consumptive Behavior - Fitri Hayati; Putra Apriadi Siregar; Reni Ria Armayani Hasibuan; Nurhayati Nurhayati; Fauziah Nasution (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
COVID-19 impacts all lines of life, from the economic impact to economic and health. COVID-19 will increase layoffs in many families, but the need for food, vitamin supplements and health care will increase. This study aims to determine the impact of COVID-19 on family financing and family consumptive behaviour during the COVID-19 pandemic. The study was conducted in January-August 2021; the sample was 999 respondents. Researchers conducted the study by disseminating information on social media Instagram, Facebook, and Twitter through google form; then participants interested and according to the inclusion criteria will be continued by filling out a questionnaire. Data analysis using the chi-square test and the prevalent rate (PR) with 95% CI. The results of this study indicate that %). There is a relationship between family layoffs with difficulties in buying family food ingredients (p<0.001; PR=2.112), difficulties in financing family medical treatment (p<0.001; PR=2.283) and difficulties in financing children's schools (p<0.001; PR=1.542 ). This study shows that families who have experienced layoffs have a 2,283 times greater risk of experiencing difficulty paying for medical costs during the COVID-19 pandemic than families who have not experienced layoffs to experience medical costs for family treatment during the COVID-19 pandemics.